2003
DOI: 10.1074/jbc.m301808200
|View full text |Cite
|
Sign up to set email alerts
|

Control of Electron Transport in Photosystem I by the Iron-Sulfur Cluster FX in Response to Intra- and Intersubunit Interactions

Abstract: Photosystem I (PS I) is a transmembraneal multisubunit complex that mediates light-induced electron transfer from plactocyanine to ferredoxin. The electron transfer proceeds from an excited chlorophyll a dimer (P700) through a chlorophyll a (A 0 ), a phylloquinone (A 1 ), and a [4Fe-4S] iron-sulfur cluster F X , all located on the core subunits PsaA and PsaB, to iron-sulfur clusters F A and F B , located on subunit PsaC. Earlier, it was attempted to determine the function of F X in the absence of F A/B mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…[11] The flash-induced transient decay, DA, at 820 and 700 nm in PS I proteins isolated from mutants D479C, showed a similar result as for the wild type, with a back reaction of 4.5 ms halftime, which should be ascribed to the reduction of P700 + by the electron-transfer mediator, phenasine methosulfate (see Supporting Information). The results indicated that electrons are mediated to F A /F B in the mutated PS I.…”
Section: By Ludmila Frolov Yossi Rosenwaks Chanoch Carmeli* and Itsupporting
confidence: 61%
“…[11] The flash-induced transient decay, DA, at 820 and 700 nm in PS I proteins isolated from mutants D479C, showed a similar result as for the wild type, with a back reaction of 4.5 ms halftime, which should be ascribed to the reduction of P700 + by the electron-transfer mediator, phenasine methosulfate (see Supporting Information). The results indicated that electrons are mediated to F A /F B in the mutated PS I.…”
Section: By Ludmila Frolov Yossi Rosenwaks Chanoch Carmeli* and Itsupporting
confidence: 61%
“…PCC 6803 was induced by homologous recombination using plasmids pZBL for induction of cysteine Y634C mutations and pBLDB for psaB interruption in recipient cells, as previously described. [4,8,9] PS I was isolated from thylakoid membranes by solubiliztion with ndodecyl b-D-maltoside and purification on DEAE-cellulose columns and on a sucrose gradient. The isolation of PS I, the analysis chlorophyll content and photochemical activity determined by flash-induced transient oxidation of P700 at DA820 and at DA700 nm were as described.…”
Section: Methodsmentioning
confidence: 99%
“…The isolation of PS I, the analysis chlorophyll content and photochemical activity determined by flash-induced transient oxidation of P700 at DA820 and at DA700 nm were as described. [9] In both the cysteine mutant and the native PS I, a half-time of 25 ms for the reduction of P700 was recorded. Surface-exposed cysteines on PS I were probed by biotin-maleimide, as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion mutants of Synechocystis for psbM, psaE, psaK or psaI typically show only limited differences in growth rate or photosynthetic electron transport compared to wild-type lines in replete medium and under low-light irradiance (Bentley et al, 2008;Chitnis et al, 1989a;Naithani et al, 2000;Xu et al, 1995). By contrast, the subunits of photosystem I and II that are typically encoded in chloroplast genomes (such as PsaA, -B, or -C and PsbA) are essential for photosynthesis, as analogous deletion mutants are unable to grow photoautotrophically (Gong et al, 2003;Jansson et al, 1987;Smart et al, 1991). The only significant exception to this is PsaD, a factor involved in binding ferredoxin to photosystem I.…”
Section: Are Certain Types Of Genes Preferentially Transferred?mentioning
confidence: 99%